Electrically tunable artificial gauge potential for polaritons - Hyang-Tag Lim (Nature Portfolio, 2017)
Artificial gauge fields promise a route to controlling topological properties of photonic systems but have only been realized by static design. Here, Limet al. demonstrate that perpendicular electric and magnetic fields can effect dynamically controlled artificial gauge potentials for polaritons.